INTEGRATION OF SCOR AND FUZZY AHP FOR LOCATION SELECTION OF EDIBLE WHITE COPRA AGRO-INDUSTRY - Wardah, Siti; Marimin, Marimin; Sudarwati, Wiwik; Marfuah, Umi (Department of Agroindustrial Technology, Bogor Agricultural University, 2023)
The selection of agro-industry location is essential in establishing, growing, and relocating agro-industrial systems for all forms of product development. In this regard, white copra has displayed a great economic potential due to export demand. To response this challenge, Indragiri Hilir Regency in Riau Province might become the most promising area since the location is lack of agroindustrial activity. Such condition leads to a excessive supply of coconut, which is in turn, causing the low price. This work aimed determine the best location for developing agroindustry for edible white copra based on multiple criteria. According to the findings, this research successfully created a new integration SCOR with Fuzzy AHP based on a multiple-criteria approach. At the first and second level, each option has equal rate of importance for each attribute and metric, while at the third level, corresponding to the highest importance, is the adaptability for increased shipping, procurement cost, days for coconut inventory, days for edible white copra stock. The fourth level, also corresponding to the highest importance, includes standard conformity, transportation facility, and the percentage of orders with the correct content. Based on the analysis, the locations showing the highest to the lowest importance were Tembilahan Hulu (0.194), Tempuling (0.152), Batang Tuaka (0.160), Kempas (0.118), Kuala Indragiri (0.100), Tembilahan (0.100), Teluk Belengkong (0.087), Pelangiran (0.080), and Enok (0.072). This research is expected to increase the development of edible white copra agroindustry in the Regency of Indragiri Hilir. Keywords: integration, SCOR, FUZZY AHP, multicriteria, edible white copra